2015
DOI: 10.1080/00461520.2015.1124022
|View full text |Cite
|
Sign up to set email alerts
|

Constructionist Gaming: Understanding the Benefits of Making Games for Learning

Abstract: There has been considerable interest in examining the educational potential of playing video games. One crucial element, however, has traditionally been left out of these discussionsnamely, children's learning through making their own games. In this article, we review and synthesize 55 studies from the last decade on making games and learning. We found that the majority of studies focused on teaching coding and academic content through game making, and that few studies explicitly examined the roles of collabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
170
1
17

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(202 citation statements)
references
References 79 publications
4
170
1
17
Order By: Relevance
“…Specifically, during this period, children's interactions with digital media are largely investigated with regard to their acquisition of content knowledge and general skills. These learning objectives are frequently based in activities that entail designing or playing digital games or engaging with simulations based in formal school settings, and to some extent, informal educational settings such as museums (see Allsop, ; Crowley, Pierroux, & Knutson, ; Evans, Norton, Chang, Deater‐Deckard, & Balci, ; Kafai & Burke, ; Kafai, Quintero, & Feldon, ; Ketelhut, Nelson, Clarke, & Dede, ). Although few studies have focused specifically on middle childhood, a meta‐analysis of studies involving K‐16 students documented benefits of digital games for learning when compared to nongame conditions (Clark et al., ).…”
Section: Media Use During Middle Childhoodmentioning
confidence: 99%
“…Specifically, during this period, children's interactions with digital media are largely investigated with regard to their acquisition of content knowledge and general skills. These learning objectives are frequently based in activities that entail designing or playing digital games or engaging with simulations based in formal school settings, and to some extent, informal educational settings such as museums (see Allsop, ; Crowley, Pierroux, & Knutson, ; Evans, Norton, Chang, Deater‐Deckard, & Balci, ; Kafai & Burke, ; Kafai, Quintero, & Feldon, ; Ketelhut, Nelson, Clarke, & Dede, ). Although few studies have focused specifically on middle childhood, a meta‐analysis of studies involving K‐16 students documented benefits of digital games for learning when compared to nongame conditions (Clark et al., ).…”
Section: Media Use During Middle Childhoodmentioning
confidence: 99%
“…The second case study, the Minecraft game environment, showed how a commercial game was further designed and implemented in a primary school after school club. This was an example of a constructivist game approach where learners played but also modified their own games (Kafai and Burke, 2015). This study showed how game experience prompted students' knowledge acquisition as well as supported students' learning skills in terms of programming and collaboration.…”
Section: Discussion-how To Design Cognitively Effortful and Affectivementioning
confidence: 88%
“…I am pretty sure I won't speak to half of the players anymore." To conclude, Minecraft is an example of a constructivist gaming experience in which players can play, modify the game, or even create their own games for learning (Kafai and Burke, 2015). In this case study, the students modified the game.…”
Section: Case 2: Games For Learning As Supporting Students' Creativitmentioning
confidence: 99%
“…Formal and informal learning researchers have found that skills practice is important to many aspects of STEM learning, such as inquiry, spatial reasoning, and computational thinking (Allen et al. ; Ansbacher ; Gutwill and Allen ; Humphrey and Gutwill ; Kafai and Burke ; National Research Council ; Newcombe et al. in press).…”
Section: Resultsmentioning
confidence: 99%